We have a religion : the 1920s Pueblo Indian dance controversy and American religious freedom - Wenger, Tisa Joy, 1969- (Published in association with the William P. Clements Center for Southwest Studies, Southern Methodist University by the University of North Carolina Press, 2009)
For Native Americans, religious freedom has been an elusive goal. From nineteenth-century bans on Indigenous ceremonial practices to twenty-first-century legal battles over sacred lands, peyote use, and hunting practices, the U.S. government has often acted as if Indian traditions were somehow not truly religious and therefore not eligible for the constitutional protections of the First Amendment. In this book, Tisa Wenger shows that cultural notions about what constitutes "religion" are crucial to public debates over religious freedom. In the 1920s, Pueblo Indian leaders in New Mexico
Keywords: Pueblo dance.; Pueblo Indians -- Religion.; Pueblo Indians -- Rites and ceremonies.; Christianity and culture -- Southwest, New.; Christianity and other religions -- Southwest, New.; Racism -- Religious aspects -- Christianity.; Religious tolerance -- Southwest, New.; Danses pueblo.; Pueblo -- Religion.; Pueblo -- Rites et cérémonies.; Christianisme -- Relations -- États-Unis (Nouveau Sud-Ouest); Tolérance religieuse -- États-Unis (Nouveau Sud-Ouest); RELIGION -- Ethnic & Tribal.; Christianity; Christianity and culture; Interfaith relations; Pueblo dance; Pueblo Indians -- Religion; Pueblo Indians -- Rites and ceremonies; Racism -- Religious aspects -- Christianity; Religious tolerance; New Southwest; Christentum; Synkretismus; Tanz; Ritus; Puebloindianer.; History